The little things [videorecording (DVD)] - Hancock, John Lee; Washington, Denzel, 1954-; Malek, Rami; Leto, Jared, 1971-; Bauer, Chris (Warner Bros. Home Entertainment, 2021)
Kern County Deputy Sheriff Joe "Deke" Deacon is sent to Los Angeles for what should have been a quick evidence-gathering assignment. Instead, he becomes embroiled in the search for a killer who is terrorizing the city. Leading the hunt, L.A. Sheriff Department Sergeant Jim Baxter, impressed with Deke's cop instincts, unofficially engages his help. But as they track the killer, Baxter is unaware that the investigation is dredging up echoes of Deke's past, uncovering disturbing secrets that could threaten more than his case.